2017
DOI: 10.7150/thno.21713
|View full text |Cite
|
Sign up to set email alerts
|

miR34a/GOLPH3 Axis abrogates Urothelial Bladder Cancer Chemoresistance via Reduced Cancer Stemness

Abstract: Rationale: Chemoresistance and subsequent recurrence of human urothelial bladder cancer (UBC) is partially driven by a subpopulation of tumor initiating cells, namely cancer stem cells (CSCs). However, the underlying molecular mechanism in chemotherapy-induced CSCs enrichment and following chemoresistance and recurrence remains largely unclear.Methods: Gemcitabine and cisplatin (GC) chemoresistant cell lines (T24 GC 3rd and 5637 GC 3rd cells) and the chemo-sensitive UBC cell lines T24 and 5637 were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 26 publications
0
47
1
Order By: Relevance
“…In bladder cancer cells, the over-expression or knockdown of GOLPH3 increases or decreases the expression of CSC factors (CD44, KLF4, ALDH1, and SOX2), respectively. The levels of miR-34-5p are down-regulated in gemcitabine-and cisplatin-resistant bladder cancer cells, contributing to enriched CSC populations [147] (Figure 2 and Table 4). Furthermore, the ability of miR-34-5p to target multiple genes (see Tables 3 and 4) can explain why this miRNA functions effectively with several chemotherapeutics.…”
Section: Golph3mentioning
confidence: 99%
“…In bladder cancer cells, the over-expression or knockdown of GOLPH3 increases or decreases the expression of CSC factors (CD44, KLF4, ALDH1, and SOX2), respectively. The levels of miR-34-5p are down-regulated in gemcitabine-and cisplatin-resistant bladder cancer cells, contributing to enriched CSC populations [147] (Figure 2 and Table 4). Furthermore, the ability of miR-34-5p to target multiple genes (see Tables 3 and 4) can explain why this miRNA functions effectively with several chemotherapeutics.…”
Section: Golph3mentioning
confidence: 99%
“…MicroRNAs (miRNAs) play a critical role in tumor progression by regulating gene expression at the posttranscriptional level. Several miRNAs, including miR-22 (20), miR-21 (21), miR-429 (22), miR-34a (23), and miR-139-5p (24), have been implicated in bladder cancer. miR-432-5p has been reported to play an important role in tumor progression.…”
mentioning
confidence: 99%
“…42 Nevertheless, the other study showed that overexpression of miR-320 could promote the invasion and metastasis of ovarian cancer. 45 Zhang et al 14 found that miR-590-3p was downregulated in GEM-resistant T24 cells, unexpectedly, upregulated in our qRT-PCR. For miR-590-3p, it could inhibit cell proliferation, cell migration, and clonogenic activity of head and neck cancer cells.…”
Section: Discussionmentioning
confidence: 50%
“…14 Interaction between differentially expressed miR-NAs and identified DEGs was retrieved using the R package multiMiR. 14 Interaction between differentially expressed miR-NAs and identified DEGs was retrieved using the R package multiMiR.…”
Section: Target Genes Prediction Of Differentially Expressed Mirnasmentioning
confidence: 99%